The influence of the football club brand on the formation of the image of the municipal territory - Shamray A.G.; Labush N.S.; Nikonov S.B.; Oleynikov S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the possibility of using the achievements of a football club to shape the image of the territory on which the club is based. Methods and structure of the study. The object of the study is the Sheriff football club. The empirical base was more than 450 publications about the activities of the club. Results and conclusions. The image of the club is not formed due to one achievement (winning a match), but, on the contrary, a number of different events, especially dramatic ones, emphasize connections with the overall promotion strategy. One of the factors in forming a positive image of Pridnestrovie in the outside world is incoming sports tourism, the flagship of which is the Sheriff football club.